2006
DOI: 10.1139/e06-010
|View full text |Cite
|
Sign up to set email alerts
|

Age constraints for Paleoproterozoic glaciation in the Lake Superior Region: detrital zircon and hydrothermal xenotime ages for the Chocolay Group, Marquette Range Supergroup

Abstract: A geochronological study of the Chocolay Group at the base of the Paleoproterozoic Marquette Range Supergroup in Michigan, Lake Superior Region, is attempted for the first time. Age data from detrital zircon grains and hydrothermal xenotime from the basal glaciogenic formation, the Enchantment Lake Formation, and the stratigraphically higher Sturgeon Quartzite and its equivalent, the Sunday Quartzite, provide maximum and minimum age constraints for the Chocolay Group. The youngest detrital zircon population in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In spite of early suggestions such as those of Young (1966) and Young and Church (1966) and that of Ojakangas (1988) and Ojakangas et al (2001b), correlation between the Palaeoproterozoic successions of the Lake Huron and Lake Superior regions was not generally accepted. New geochronological work on detrital zircons and xenotime cements from rocks of the Chocolay Group in northern Michigan (Vallini et al 2006) provided convincing data in support of the old correlations. The new age data showed that the depositional age of the Chocolay Group, including the glaciogenic diamictites at its base, is probably between about 2.3 and 2.2 Ga, thus validating the lithostratigraphic correlation proposed 40 years earlier.…”
Section: Other Occurrences Of Palaeoproterozoic Glaciogenic Rocks In mentioning
confidence: 67%
See 1 more Smart Citation
“…In spite of early suggestions such as those of Young (1966) and Young and Church (1966) and that of Ojakangas (1988) and Ojakangas et al (2001b), correlation between the Palaeoproterozoic successions of the Lake Huron and Lake Superior regions was not generally accepted. New geochronological work on detrital zircons and xenotime cements from rocks of the Chocolay Group in northern Michigan (Vallini et al 2006) provided convincing data in support of the old correlations. The new age data showed that the depositional age of the Chocolay Group, including the glaciogenic diamictites at its base, is probably between about 2.3 and 2.2 Ga, thus validating the lithostratigraphic correlation proposed 40 years earlier.…”
Section: Other Occurrences Of Palaeoproterozoic Glaciogenic Rocks In mentioning
confidence: 67%
“…Early attempts at lithostratigraphic correlation of these ancient glacial deposits were frustrated by spurious age data and erroneous interpretations of these data but as geochronological techniques have become more sophisticated, new results are showing that many of the early lithostratigraphical correlations are correct. Correlation of the Gowganda Formation with thinner glaciogenic deposits in Northern Michigan is now supported by modern geochronology (Vallini et al 2006). Deposition of Palaeoproterozoic sedimentary rocks in the N. Michigan area was initiated at the time of deposition of the Gowganda Formation so that the earlier glaciogenic formations and associated rocks are not preserved there.…”
Section: Summary Of North American Occurrences Of Palaeoproterozoic Gmentioning
confidence: 98%
“…The Chocolay Group of the Marquette Range Supergroup consists of diamictite (Enchantment Lake Formation), sandstone (Mesnard Formation), and carbonate (Kona Dolomite) in ascending stratigraphic order (Figure 1b). The depositional age of the Enchantment Lake Formation has been constrained to between 2.29 and 2.13 Ga [ Vallini et al , 2006]. Positive δ 13 C carb excursions that may represent the onset of the Lomagundi event have been observed in the Kona Dolomite [ Bekker et al , 2006].…”
Section: Introductionmentioning
confidence: 99%
“…The age constraints for the Huronian Supergroup are from Young et al [2001] and Bekker et al [2006, and references therein]. The age constraint for the Enchantment Lake Formation is given by Vallini et al [2006].…”
Section: Introductionmentioning
confidence: 99%
“…Lithostratigraphical correlation between Palaeoproterozoic rocks on the north shore of Lake Huron and the south shore of Lake Superior. Note that there is only one glacial formation in each of the sections in the Lake Superior area and these are correlated with the Gowganda Formation of the Huronian Supergroup, as validated by recent geochronological studies (Vallini et al ., ). The glacial deposits of both regions are followed by quartz arenites.…”
Section: Palaeoproterozoic Glaciationsmentioning
confidence: 97%